Perfil metabólico por RMN de 1H e avaliação citotóxica do fungo endofítico Colletotrichum gloeosporioides isolado de Eugenia jambolana, em diferentes meios de cultivo - Borges, Fernando Monteiro [UNESP] (2014)
Endophytic fungi are microorganisms that asymptomatically colonize the interior of plants, being found in plant organs such as leaves, stems, fruits, seeds and roots, the plant may dwell for a lifetime, and are transmitted in some cases, for future generations through seed host. These exhibit specific ecological interactions in its habitat that has been little explored as a strategy for the discovery of new bioactive natural products. Among the various modifications of culture media to stimulate and increase silent biosynthetic pathways and metabolic production, OSMAC (One Strain Many Compounds) technique was used in this work. Colletotrichum gloeosporioides isolated from Eugenia jambolana was grown in two different kind of media: two nutrient solids (rice and maize) and five nutrient liquids (Czapek, Malte, Nutrient, PDB and YM) in the presence and absence of polyethylene as a solid support network, to evaluate the variation in the production of secondery metabolites. With the change of the culture media, we observed high metabolic variation in all media, which was corroborated by analysis by 1H NMR and HPLC-DAD. For cultivation in malt extract in the presence of the solid support network (polyethylene) was observed a mass increase of approximately 275% in cultivation. The extracts EjC(05)Arroz, EjC(05)YmSR, EjC(05)MaltSR and EjC(05)MaltCR showed antitumor potential against OVCAR (ovarian carcinoma), HCT -116 (human colon) strains and SF- 295 (human glioblastoma). Evaluation of all crude extracts allowed select the EjC(05)MaltCR for dereplication of substances produced, making it possible to identify the diketopiperazines Cycle Proline-Valine and Cycle Proline-Leucine/Isoleucine.